Strategi Komunikasi Dinas Perhubungan Kota Serang dalam Sosialisasi Kebijakan Program Sistem Satu Arah Jalan Kaujon Serang - Laksana, April; Ferdiana, Riska; Hanafi, Mansur (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2024)
Traffic congestion is a common phenomenon in many major cities, including the Kaujon area in Serang. Kaujon is one of the densely populated areas in the city of Serang, which has experienced rapid growth in recent years. The high population growth, supported by the development of infrastructure and the local economy, has led to transportation problems, particularly traffic congestion, becoming increasingly concerning. The objective of this research is to understand the communication strategies and steps taken by the Serang City Transportation Department in socializing the One-Way System Program Policy. This research uses a descriptive qualitative approach and employs a case study, which involves using empirical evidence from one or more cases to study the problem within its context. The results of this study reveal that the Serang City Transportation Department employs communication strategies to socialize the One-Way Kaujon policy to the community. These socialization efforts involve various approaches, including but not limited to the following: 1) Operational Approach; 2) Persuasive and Educational Approach; 3) Coordinative Approach. As a result, information about and the policy of the One-Way System can be conveyed and implemented in Kaujon, Serang City, for the smooth flow of traffic on the city's roads.